THE POLITICAL OVERREPRESENTATION OF THE MOST DEVELOPED REGION: AN ELECTORAL GEOGRAPHY ANALYSIS OF MINAS GERAIS (GEOgraphia, 2025)
Does the Brazilian electoral system produce equitable outcomes in the context of deep regional inequalities? The goal of this article is to address this question from the perspective of the “one person one vote” principle. While territorial constituencies are fundamental in Single Member Districts (SMDs), they tend to be overlooked in Multimember Districts (MMDs). To test this hypothesis, this study examines the socioeconomic disparities between the officially defined regions in the state of Minas Gerais. By identifying Belo Horizonte and Teófilo Otoni as the intermediate regions with the greatest disparity, a comparison was made of the number of elected representatives between 1998 and 2022. The results reveal the political overrepresentation of Belo Horizonte at the expense of Teófilo Otoni.